DIGITAL FREEDOM OF EXPRESSION: COMPARATIVE LEGAL MODELS IN INDONESIA, CHINA, AND UNITED STATES OF AMERICA - Andes Robensyah (KANUN:JURNAL ILMU HUKUM, 2026)
The rapid evolution of digital technology has made freedom of expression a critical transnational issue, yet a legal gap exists in how national implementations diverge from uniform international standards like the International Convention on Civil and Political Rights (ICCPR). Previous research often lacks a cross-border perspective, leaving a void in understanding how contrasting political philosophies impact digital rights. This study addresses the question of how digital expression is governed under three distinct legal ideologies: the constitutional democratic, digital authoritarian, and constitutional liberal models.Using comparative legal research methods, the study analyzes the legal frameworks, norms, and practices of Indonesia, China, and the United States of America (USA). Key findings reveal that Indonesia employs a mixed model; while the 1945 Constitution guarantees rights, the ITE Law has historically caused a "chilling effect" through vague defamation articles. However, recent 2024–2025 Constitutional Court rulings have narrowed these norms to protect criticism of government agencies. China adheres to a restrictive model centered on "cyber sovereignty" and national stability, using the Cybersecurity Law and selective censorship to suppress collective social mobilization. In contrast, the USA follows a maximalist approach rooted in the First Amendment and Section 230 platform immunity, which protects broad freedom but creates a dilemma regarding unchecked disinformation.This article contributes a cross-jurisdictional analysis that transcends domestic mapping. It provides practical value for policy reform, suggesting that Indonesia can find a democratic balance by learning from the strengths of the American liberal model and the pitfalls of the Chinese control approach.